A longitudinal controlled signage intervention to increase stair use at university buildings: Process and impact evaluation using RE-AIM framework - Muttaqien, Zaenal; Wasityastuti, Widya; Sofyana, Meida; Agustiningsih, Denny; Wibowo, Rakhmat Ari (Frontiers in Public Health, 2023)
Introduction: Stair climbing intervention could be suggested to address low occupational physical activity among university students and employees. Strong evidence showed the effectiveness of signage intervention in increasing stair use in public areas. However, evidence in worksite settings, including university settings, was inconclusive. This study aimed to evaluate the process and impact of a signage intervention to increase stair use at a university building using the RE-AIM Framework. Method: We conducted a non-randomised controlled pretest-posttest study to examine the effect of signage intervention placed in university buildings in Yogyakarta (Indonesia) between September 2019 and March 2020. The process of designing the signage involved the employees in the intervention building. The main outcome was the change in the proportion of stair use to elevator use measured by manual observations of video recordings from closed-circuit television. A linear mixed model examined the intervention effect by controlling the total visitor count as a confounder. RE-AIM framework was used in the process and impact evaluation. Results: The change in the proportion of stair climbing from baseline to the 6th-month phase at the intervention building (+0.067 (95% CI = 0.014 to 0.120) was significantly higher than that of the control building. However, the signs did not change the proportion of the stair descending at the intervention building. The signs were potentially viewed 15077 to 18868 times/week by visitors. Conclusion: Signage intervention using portable posters could easily be adopted, implemented, and maintained in similar settings. A co-produced low-cost signage intervention was found to have a good reach, effectiveness, adoption, implementation, and maintenance dimension.